Cortical hierarchy turned on its head - Buchel, Christian (Nature neuroscience, 2003)
Sighted people devote much their cortex to visual processing, but in the blind, 'visual' areas are recruited for other senses. A paper in this issue now reports that V1 in the blind is also activated by a verbal memory task, without any sensory input.